Dampak Literasi Digital Pasien terhadap Kepuasan Pasien untuk Aplikasi Kesehatan - Mauliatesi Matas (Journal Health Information Management Indonesian (JHIMI), 2023)
Information technology has become a human need in all aspects of life, in which humans in this era take advantage of the sophistication of information technology, including the health sector. Using technology needs some skill include digital literacy. Digital literacy is the skill and ability to master and make use the information from digital sources including computers, smartphones, and laptops that can create a critical and creative mindset and perception. User Satisfaction is a person’s pleasure from comparing what the user expects from the apllication and the results are as expected. Patient satisfaction assessment in that application never been done. The aim of this study is to know the effect digital literacy skill to patient satisfaction as user of the application Hospital X. Design of this study is cross sectional. Sample in this study is 99 respondents. The sampling technique is through quota sampling. The data analysis technique uses a simple linear regression test. The result of this study explained that there was a significant effect between digital literacy with patient satisfaction as user of the heath application, with p value =0,023. Correlation value is 0,228. Digital literacy effected 5,2% toward patient satisfaction as user of the health application in Hospital X